Quality management in plastics processing : strategies, targets, techniques and tools - Kent, Robin John (Elsevier, 2016)
Provides a structured approach to the techniques of quality management, also covering topics of relevance to plastics processors. The book's focus isn't just on implementation of formal quality systems, such as ISO 9001, but about real world, practical guidance in establishing good quality management. Ultimately, improved quality management delivers better products, higher customer satisfaction, increased sales, and reduced operation costs. The book helps practitioners who are wondering how to begin implementing quality management techniques in their business focus on key management and technical issues, including raw materials, processing, and operations. It is a roadmap for all company operations, from people, product design, sales/marketing, and production - all of which are impacted by, and involved in, the implementation of an effective quality management system.